2020
DOI: 10.3389/fmicb.2020.557253
|View full text |Cite
|
Sign up to set email alerts
|

Sixty-One Volatiles Have Phylogenetic Signals Across Bacterial Domain and Fungal Kingdom

Abstract: Microorganisms are diverse in their genome sequences and subsequently in their encoded metabolic pathways, which enabled them to adapt to numerous environmental conditions. They produce thousands of small molecules, many of which are volatiles in nature and play important roles in signaling in intra-and inter-species to kingdom and domain interactions, survival, or virulence. Many of these compounds have been studied, characterized, and organized in the mVOC 2.0 database. However, such dataset has not been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…1-octen-3ol is a characteristic fragrance compound produced by Aspergillus, such as Aspergillus luchuensis (Kataoka et al, 2020), Aspergillus flavus (Miyamoto et al, 2014), and so on. Moreover, 2-pentylfuran was commonly known and definitely confirmed to be produced primarily by fungal genera in the report of Elmassry et al (2020). Therefore, it could be inferred that certain amounts of fungi might be existing in our mutton sausage.…”
Section: Volatile Flavors Of Mutton Sausage During Ripeningsupporting
confidence: 52%
“…1-octen-3ol is a characteristic fragrance compound produced by Aspergillus, such as Aspergillus luchuensis (Kataoka et al, 2020), Aspergillus flavus (Miyamoto et al, 2014), and so on. Moreover, 2-pentylfuran was commonly known and definitely confirmed to be produced primarily by fungal genera in the report of Elmassry et al (2020). Therefore, it could be inferred that certain amounts of fungi might be existing in our mutton sausage.…”
Section: Volatile Flavors Of Mutton Sausage During Ripeningsupporting
confidence: 52%
“…Isovaleric acid, isobutyric acid, and 2-methylbutanoic acid are short-chain fatty acids. Isovaleric acid is usually produced by a large number of bacteria rather than fungi . Researchers found that isovaleric acid not only inhibited the mycelial growth of Fusarium oxysporum and Moniliophthora perniciosa but also inhibited the biofilm formation of Staphylococcus epidermidis by reducing polysaccharide synthesis. , Isobutyric acid, the main volatile component of the first commercial microbial fumigant, Muscodor albus, is usually monitored as an indicator of antifungal activity .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is beneficial to the production of 2,3-BD under acidic conditions, consequently indicating that acetic acid exerts an indispensable role in the entire production process of 2,3-BD. At the same time, studies have been shown that acetic acid can be used as a signal molecule to affect cell membranes, bacteriocins and QS (Elmassry et al 2020;Ge et al 2019). Therefore, it can also be believed that in the S. cerevisiae quorum sensing system, acetic acid has the potential as a signal molecule.…”
Section: Discussionmentioning
confidence: 99%